Biology of green mussel (Perna viridis) in selected culture sites along Villareal Bay, Villareal, Samar, Philippines. - Toralde, Cherryhel B. (Cherryhel B. Toralde, 2019)
The aquaculture of Perna viridis in Villareal Bay was the largest supplier of green mussels in Eastern Visayas in the year 2018. Despite its huge contrinution to the countrys mussel industry, no comprehensive assessment on its biology was ever done in this bay. This paper presents the mussel's growth, sex distribution, reproductive status, condition, as well as the bay's environmental condition and phytoplankton community. Overall, 360 samples ranging from 16.10 mm to 107.30 mm long were collected from December, 2018 to March, 2019 in two selected culture sites. Environmental conditions of the bay suggests that it is still suitable for P. viridis aquaculture. Mussel growth were shown to exhibit different patterns and is highly correlated to the water's TSS levels. Low CI values and growth rates confirmed that mussels undergo spawning in January for Site 1 and in February for Site 2. Appropriate harvest seasons are hence proposed to coincide with high CI values, and that is in February and March for Sites 1 and 2, respectively. N. scintillans, a voracious graer of diatoms probably competed with P. viridis for food. This study may help our local farmers develop a more sustainable mussel culture as it discusses the factors influencing the growth and development of P. viridis farmed in this bay.